1996
DOI: 10.1002/elps.1150170805
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity in acatalasemia

Abstract: 203 bp long products containing exon 4 and its junctions from the catalase gene were generated by polymerase chain reaction (PCR). These products were analyzed by single strand conformational polymorphism (SSCP), hetero-duplex formation and nucleotide sequencing. No polymorphism was detected when the Hungarian acatalasemic sisters, their family members and normocatalasemic controls were analyzed. Sequence analyses did not show the G to A point mutation at position 5 of intron 4. This splicing mutation characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In contrast, none of the 66 normocatalasemic family members suffered from diabetes mellitus [13,14]. Genetic analysis of these families showed that the known types of Japanese acatalasemia (2) were not found in the Hungarian families [15,16].…”
Section: Introductionmentioning
confidence: 76%
“…In contrast, none of the 66 normocatalasemic family members suffered from diabetes mellitus [13,14]. Genetic analysis of these families showed that the known types of Japanese acatalasemia (2) were not found in the Hungarian families [15,16].…”
Section: Introductionmentioning
confidence: 76%
“…We have reported on two acatalasemic sisters in the first Hungarian acatalasemic family [9] and nine hypocatalasemic families [10] with 37 hypocatalasemics including the biochemical markers of lipid and carbohydrate metabolism in acatalasemia and hypocatalasemia [11]. In Hungarian acatalasemic and hypocatalasemic patients, we could not detect the mutations responsible for the defect catalase synthesis in Japanese patients [12,13]. For the acatalasemic and three hypocatalasemic families, we found a GA insertion at position 138 of exon 2.…”
mentioning
confidence: 83%
“…The biochemical characterization of their catalase protein revealed a difference from the Swiss type and similarity to the Japanese type of this syndrome [8]. In contrast to this similarity, the lack of G to A mutation at the fifth position of intron four for Hungarian acatalasemic patients revealed genetic heterogeneity in acatalasemia between Caucasians and Japanese [9]. Heterozygotes of Hungarian acatalasemia showed half the normal blood catalase (hypocatalasemia) activity, similar to the Japanese patients [lo].…”
mentioning
confidence: 99%